The Authentication Landscape in 2019: One Does Not Simply Walk into Order. Issue 1 (1st June 2020) - Arsenault, Jeff; Dresselhaus, Angela; Tokoro, Shoko; Twardowski, Kristen
ABSTRACT: Over the last decade, access authentication has rapidly evolved. An overview of various e-resource access management types, including Internet Protocol (IP) authentication, referring and embedded URLS, barcode patterns, and user accounts with publishers, shows that though IP authentication has dominated the authentication landscape, it creates many security problems and does not offer a pleasant user experience. The standardization of single sign-on solutions as formulated by the National Information Standards Organization's (NISO) initiative, Resource Access for the 21st Century (RA21), and continued by the Seamless Access Coalition since June 2019, seeks to improve both the discovery experience and security protocols. Two case studies, one from the University of North Carolina, Charlotte and the other from Eastern Carolina University, explore the benefits, pitfalls, and practical realities of moving from an IP authentication system, EZproxy, to a single sign-on system, OpenAthens.